Discrepancy of the effect of maternal smoking during pregnancy on trajectories of gestational weight gain and estimated fetal weight - Kohta Suzuki; Rei Wakayama; Zentaro Yamagata (Tobacco Induced Diseases, 2019)
Objective To examine the difference of the effect of maternal smoking during pregnancy on trajectories of gestational weight gain (GWG) and estimated fetal weight (EFW) by using multilevel models